Inhibitory effect of kaempferol on skin fibrosis in systemic sclerosis by the suppression of oxidative stress. Issue 1 (October 2019) - Sekiguchi, Akiko; Motegi, Sei-ichiro; Fujiwara, Chisako; Yamazaki, Sahori; Inoue, Yuta; Uchiyama, Akihiko; Akai, Ryoko; Iwawaki, Takao; Ishikawa, Osamu
Highlights: Kaempferol suppressed the bleomycin-induced dermal fibrosis in mice. Kaempferol reduced oxidative stress in the bleomycin-induced fibrotic skin in vivo . Kaempferol reduced inflammatory/fibrotic cytokines in bleomycin-treated skin. Kaempferol reduced bleomycin-induced apoptosis in vivo. Kaempferol reduced oxidant-induced ROS and apoptosis in SSc fibroblasts in vitro. Abstract: Background: There is growing evidence that vasculopathy-induced hypoxia and oxidative stress enhance the process of fibrosis in systemic sclerosis (SSc). Kaempferol is a natural flavonoid widely found in various vegetables and fruits, and has been reported to have excellent antioxidant activity. Objective: Objective was to elucidate the effect of kaempferol on skin fibrosis and the mechanism of the inhibitory regulation of fibrosis by kaempferol. Methods: We assessed the effect of intraperitoneally administered kaempferol on bleomycin-induced dermal fibrosis in mice. The effect of kaempferol on oxidative stress in bleomycin-treated mice and SSc fibroblasts was assessed in vivo and in vitro . Results: We identified that kaempferol injection significantly inhibited bleomycin-induced dermal fibrosis in mice. The number of αSMA + myofibroblasts, CD3 + T-cells, and CD68 + macrophages in lesional skin was significantly decreased by kaempferol injections. Kaempferol administration also significantly suppressed the bleomycin-induced oxidative stress signal in OKD48 mice. Additionally, mRNA levels of oxidative stress-associated factors, such as HO-1 and NOX2, as well as inflammatory and pro-fibrotic cytokines, including IL-6, TGF-β and TNFα in sclerotic skin were significantly decreased by kaempferol. Kaempferol also reduced bleomycin-induced TUNEL + apoptotic cells in the lesional skin of bleomycin-treated mice. Furthermore, the oxidant-induced intracellular accumulation of reactive oxygen species (ROS) in SSc fibroblasts was inhibited by kaempferol treatment. In addition, the oxidant-induced apoptosis of SSc fibroblasts was decreased by kaempferol in vitro . Conclusion: Kaempferol might improve bleomycin-induced fibrosis by reducing oxidative stress, inflammation, and oxidative cellular damage. Administration of kaempferol might be an alternative treatment for skin fibrosis in SSc.